Rebalancing Unemployment Benefits in a Unionized Labour Market. - Claus Thustrup Hansen; Hans Jørgen Jacobsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
The basic trade union model is extended to allow for a more sophisticated unemployment benefit system consisting of two benefit levels, one for short-term and one for long-term unemployed, and a rule determining whether an unemployed is short- or long-term. The purpose of this extension is twofold; to get a more realistic analysis of the actual benefit systems in most countries, and to analyse alternative reforms to the traditional one of changing a uniform benefit level. Reforms that rebalance the benefit rates holding constant either expected utility of an unemployed, aggregate benefit expenditures, or aggregate utility of union members can reduce unemployment.
Keywords: 330